Data supporting 'Understanding the effects of Digital Elevation Model resolution in urban fluvial flood modelling' - Muthusamy, Manoranjan; Rivas Casado, Monica; Leinster, Paul; Butler, David (Cranfield University, 2023)
This HERAS 2D model setup files and results were produced to study the effect of DEM resolution in fluvial flood modelling using Cockermouth storm Desmend flood (2015). -Link to the publication will be added once available- Note: This folder contains DEM data downloaded from Environment Agency, UK. This metadata record is for Approval for Access product AfA458. Attribution statement: (c) Environment Agency copyright and/or database right 2019. All rights reserved
Keywords: Digital Elevation Model'; 'Resolution'; 'Fluvial flood'; 'Urban flood'; 'Flood extent'; 'Flood depth'; 'Hydrology'; 'Environmental Science'; 'Photogrammetry and Remote Sensing'